Analysis of the Influence of Brand Image and Online Promotion on the Purchase Decision of Kopi Kenangan Products by Generation Z at Kopi Kenangan Sulawesi Surabaya - Ramadhan, Akmal Nugraha; Setyadi, Taufik; Rizkiyah, Noor (Jurnal Social Economic of Agriculture, 2025)
This study investigates the impact of brand image and online promotion on the purchasing decisions of Generation Z consumers at the Kopi Kenangan branch located in Sulawesi, Surabaya. Utilizing a quantitative research approach, data were collected from 100 respondents aged 20"“27 years through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of WarpPLS 7.0 software. The findings reveal that both brand image and online promotion exert a significant and positive influence on consumer purchase decisions. Online promotion demonstrates a greater effect, underscoring its relevance in engaging digitally active consumers. These results imply the necessity for firms to enhance digital marketing strategies and cultivate a strong brand image to effectively influence Generation Z's purchasing behavior.